On SAS-Injective Rings - Chyad, Heba Hadi; Mehdi, Akeel Ramadan (Iraqi Journal of Science, 2024)
Let be a ring. A right -module is called SAS- -injective (where is any right -module) if every right -homomorphism from a semiartinian small right submodule of into extends to . A ring is called right SAS-injective if is SAS- -injective module. Right SAS-injective rings are studied in this paper. Many characterizations and properties of this type of rings are obtained.